Evaluasi Sistem Informasi Akuntansi Atas Prosedur Penerimaan Dan Pengeluaran Kas Dana Program Bantuan Operasional Sekolah (BOS) Dalam Kaitannya Pengendalian Internal Pada Sekolah Dasar Negeri 23 Pemangkat - B51110074, Muhammad Irfan Has (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Accounting information system is a system of record, collect, classify data or information resulting from the transaction. Appropriate information systems can helping management to create planning of programs and operating activities of the school to achieve the objectives. In addition, for making accounting information system can operate effectively and efficiently, the management needs to make the internal control system. Internal controls are designed to prevent, detect, and correct their errors or irregularities that occur in accounting information systems. The results showed that SD Negeri 23 Pemangkat has a system of accounting information on receipts and cash disbursements BOS funds which overall has been effective, but has the disadvantage in terms of organizational structure. Implementation of accounting information system design is good but not yet forming into flowchart design on accounting information systems. Evaluation of internal control over cash receipts and disbursements in the implementation of BOS program using internal control questionires method showed highly effective results. Similar results were also obtained through compliance test method with the percentage of effectiveness was 82%. Â  Key word : Accounting Information System, Internal Control, BOS fund